Transparent ferroelectric transducers for flexible haptic feedback touch devices - Fook, Tony Hiu Tung (Nanyang Technological University, 2021)
Relaxor ferroelectric polymers (RFPs), a class of electroactive polymers (EAPs), have shown immense potential for haptic feedback and pressure sensing surfaces. RFPs can be applied in flexible electronics due to its excellent electromechanical properties, flexibility, light weight, mechanical toughness and ease of processing. A major advantage of RFPs such as PVDF-based terpolymers over other EAPs is its excellent optical properties, allowing for integration into devices where transparency is required, such as a haptic film directly mounted on a touch screen. However, a key drawback of RFP actuators is the high voltage needed for actuation compared to other actuator technologies. Common methods to overcome this issue such as adding nanofillers into the EAP matrix for dielectric property enhancement results in a degradation in the electric breakdown strength, dielectric loss and mechanical properties. Achieving enhanced dielectric properties while maintaining a good electric breakdown strength proves to be a challenge.